(untitled) (Revista de Estudios Brasileños, 2018)
The present study investigates Sexual Division of Labor in urban Brazil in the years of 2001 and 2014, considering different family compositions in which men and women are inserted. The hypothesis is that there are disparities in the division of labor: despite the changes that have been occurring in society throughout the years, women still have greater participation in typical activities of family care and householding. A comparative exploratory analysis was carried out between 2001 and 2014, comparing occupations, working hours, labor remuneration and education, of men and women, married and unmarried, with or without children, family heads and spouses. It was found that there was no reduction of disparities, only a reconfiguration of Sexual Division of Labor in such a way that a gender system is maintained, confirming the research hypothesis.